Contratos náuticos y estructura fractal de las normas jurídicas (fletamento vs. transporte marítimo de mercancías: del contrato, a la institución) - Garcia Pita, José Luis (Revista de Derecho, 2019)
The classic question referring the limits between the different tipes of maritime contracts,and -concretely- between Freightments and Contracts of Carriage of Goods bySea frequently suffers or is submitted to sudden turns and twists, during the process ofspanish Maritime Law Reform. The Proposal of a new General Act, proposed by Socialistsparliamentary Group, which is -“ad pedem litterae”- the same that the older 2008/Project, defines the “Freightment Contract” [Contrato de Fletamento] in terms of full andabsolute identification or equalization with the Contrac of Carriage of Goods by Sea, withthe self-evident purpose of making the Owner -which is called “Carrier”- liable for thecarriage and custody of the goods on board, and thus erasing completely the older figureof the “Contrato de Fletamento” [Freightment], as a contract for the furniture of navigationservices, for others´ account and under other’s instructions. It is done, this way, a “tabularasa” of contractual Shipowner’s will, substituing his consent in obligating to carry andcustody the goods by some kind of “receptum” or “involuntary bailment”, with deep rootsin English Law, that distorts the nature of Freightment and Transport [or Carriage], ascontracts, fruit of the private will and of his legitimate auto-normative power
Keywords: Freightment; carriage of goods; tonnage or volume agreement; freedom of contract; contract; institution; fractal geometry; seed of fractal object